Simulation Study of the Spread of Mealybugs in a Cassava Field: Effect of Release Frequency of a Biological Control Agent - Promrak, Jairaj; Rattanakul, Chontita (Agriculture and Natural Resources, 2015)
Cellular automata and Monte Carlo simulation techniques were employed to study the spread of mealybugs (a major cassava insect pest) in a cassava field. There are various recommended instructions on how often farmers should release green lacewings (a biological control agent) to control the spread of mealybugs. In this study, the effects of different release frequencies of green lacewings in controlling the spread of mealybugs were investigated.